ANALISIS TINGKAT PEMBIAYAAN BANK UMUM SYARIAH TAHUN 2007-2016 - Selva Kurnia Oneestasya; Idah Zuhroh; Muhammad Sri Wahyudi Suliswanto (Jurnal Ilmu Ekonomi JIE, 2018)
This study aims to describe the characteristics of Third Party Fund (DPK), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR) and total assets as well as to examine the effect of third party funds (DPK), Capital Adequacy Ratio (CAR), Financing to deposit Ratio (FDR) and total assets simultaneously and partially to finance the Islamic Banks Year 2007-2016.The analysis technique used in this research is multiple linear regression. The hypothesis tests use t-test (to test the effect of variable partial) and F-test (test the effect of variables simultaneously) with significance level of 5% (0:05). The results shows that simultaneously affect independent variables (DPK, CAR, FDR and total assets) The dependent variable (financing) amounted to 99.74%, while the other 0. 26% are influenced by other factors not disclosed in this study. Partially DPK, FDR and total assets have positive and significant effect. While CAR no significant positive effect on the financing of Islamic Banks Year 2007-2016.Keywords : Capital Adequacy Ratio, Third Party Funds, Financing to Deposit Ratio and Distribution of Funds